KESALAHAN PENULISAN KALIMAT TIDAK BAKU PADA KARANGAN DESKRIPSI MAHASISWA ASAL THAILAND DI LINGKUNGAN UNIVERSITAS ISLAM DARUL ‘ULUM LAMONGAN - Ihsan, Bisarul (University of Brawijaya, 2020)
Writing errors can include the use of basic words, use of capital letters, prefixes, prepositions, abbreviations, clits, re-words, or the use of punctuation. Mistakes of this kind can be caused by inaccuracy and the ability of the author in terms of authorship rules. This research aims to record the forms of errors that occur in the writing of students from Thailand in the environment of Universitas Islam Darul ‘Ulum Lamongan. This study uses a descriptive qualitative method with the subject of students from Thailand who are in the Universitas Islam Darul ‘Ulum Lamongan as many as 20 students. Data collection techniques used in this study include tests, listening, and note taking. The results of this study are the only errors in the form of writing nonstandard sentences in the form of (1) errors in the use of interference sentences, (2) reduplication errors, (3) errors in affix removal, (4) errors in the use of affixes.